Interventions to Reduce Exposures in the Workplace: A Systematic Review of Intervention Studies Over Six Decades, 1960–2019 - Johan Ohlander; Hans Kromhout; Martie van Tongeren (Frontiers in Public Health, 2020)
Background: Reducing occupational ill-health from chemical and biological agents is realized primarily through the mitigation and elimination of hazardous exposures. Despite evidence of declining exposure in European and North-American workplaces, comprehensive studies of the effectiveness of workplace interventions for reducing hazardous exposure and associated work-related ill-health seem rare. We reviewed occupational intervention studies targeting exposure to chemical and biological agents, and determined trends in frequency and quality of such studies.Methods: We searched Embase, Medline, and Web of Science for peer-reviewed original articles on occupational intervention studies published 1960–2019, aimed at reducing workers' exposure to dusts, gases, fumes, or liquids of chemical, biological, or mineral nature, or workers' risks for associated health outcomes. The frequency of articles, intervention types, intervention endpoints, and study quality of published intervention studies between 1960 and 2019 and according to 10-year intervals were analyzed.Results: Of 3,663 retrieved articles, 146 intervention studies were identified and reviewed, of which 63 concerned control measures, 43 behavioral change, 28 use of personal protective equipment, and 12 workplace policies. Intervention endpoints were occupational exposures (73%), health outcomes (22%), and a combination of both (5%). Of reviewed studies, 38% involved a control group, 16% randomized the intervention, 86% were planned interventions, and 86% compared exposure or health outcomes pre and post intervention. Over time the number of intervention studies identified in this search increased from none during 1960–1969 to ~60 during 2000–2009 and 2010–2019, respectively. The study quality improved over time, with no studies during 1960–1989 that complied with the highest quality criteria. During 2000–2009 and 2010–2019 16 and 12% of studies, respectively, were judged to be of highest quality.Conclusion: Despite an improvement over the last six decades in the frequency and quality of intervention studies targeting exposure to chemicals and biological agents, the absolute number of intervention studies remains low, particularly when considering only high quality studies. Occupational exposure to chemical and biological agents is still causing excessive disease in workforces worldwide. To reduce occupational ill-health caused by these exposures, it is important to expand the evidence on (cost-)effectiveness and transferability of interventions to reduce exposure and health effects.